INVENTARISASI JENIS TANAMAN DI KAWASAN TAMAN WISATA ALAM PULAU SANGALAKI BERAU - M Masrudy (Politeknik Pertanian Negeri Samarinda, 2017)
The experiment was conducted to know crop type in Sangalaki island in Berau. The experiment was conducted for approximately two month, since on the date of 1 Nopember to 30 Desember 2016. The methods for stocktaking of crop type was directly method that was stocktaking of all crop type residing in Nature Tour Garden area Sangalaki island in Berau with the broadness ± 15,9 Ha.The result of experiment showed that found 41 crop type, they were: Cocos nucifera, Terminalia catappa, Moringa oleifera, Pandanus amaryllifolius, Pandanus tectorius, Calophyllum inophyllum, Canavalia maritima, Derris sp., Pomotia pinnata, Phascolus marinus, Desmodium sp., Pleomclc sp., Dillenia grandifolia, Ficus benjamina, Ficus elastic, Ipomoea pes-caprae, Scaevola sp., Wedelia biflora, Morinda citrifolia, Asplenium nidus L., Barringtonia asiatica, Cassytha filiformis, Spinifex littoreus, Euphorbia atoto, Tournefortia sp., Pandanus amaryllifolius, Polyalthia longifolia, Cyperus rotundus L., Cromolaena sp., Musa sp., Mikania sp., Ocimum basilicum, Crotalaria mucronata, Euphorbia tirucalli L., Euphorbia sp., Scaevola sp., Crynum sp., Cyperus sp., Carica papaya L., Pedilanthus tithymaloidcs an Nephrolepis falcate.